The influence of information technology towards better Muslims community. - Al-Safi, Hassen Mohammed; Setiabudi, Arya, Detarbeqo; Krasniqi, Arber; Yusuf, Habibullah; Mahmood Sanusi, Mohamed; Muhammad, Muhd. Rosydi (IIUM Press, 2011)
Information technology (IT) refers to numerous forms of information exchange among two or more computers through the interconnection by using internet. A few decades ago, most of the Islamic literature(s) were only accessible in the limited location and place. For example, in the mosques, Islamic schools and libraries. Muslims communities in the west were suffering getting information related to Islam due to the lack of sources available during that time. But now Muslims around world has become aware about the use of information Technology in spreading the Islamic literature all over the world. This paper shows the significance influence of information technology towards Muslims world.